World’s Agricultural Production and Trade: Food Security at Stake? - Somai, MiklÃ³s (International Journal of Biotechnology for Wellness Industries, 2013)
The extraordinary events of the last couple of years, like the surge and the topsy-turvy movement in oil, raw material and food prices, or the development of a so far unprecedented global financial and economic crisis, have been heavily testing the endurance of those earning their living from agriculture and related activities. All these troubles have not been beneficial to the ongoing trade liberalization process within the framework of WTO. Answers to the challenges at national level and the continuing proliferation of inter- and intraregional free trade agreements make the early global liberalization even less probable. The situation is further complicated by those really divergent changes of agricultural policy that are about to develop on the opposite sides of the Atlantic. In this paper, we describe the recent development of world’s agricultural production and trade; offer an insight into the evaluation problems of worldwide food insecurity; and briefly compare the upcoming agricultural policy reforms in Europe and the US.